A Study of COVID-19 Effects on the Identity Theft Landscape - Horn, Trang Thi Thu; Yousef, Mahmoud (Engineering And Technology Journal, 2024)
This research studies the impact of COVID-19 on the identity theft landscape using historical data published by the Federal Trade Commission. The data set included information about the number of identity theft reports for each state per year over a 6-year period, 2017 -2022. The dataset also included the number of reports for each identity theft category, providing a holistic view of the identity theft landscape. The data showed a significant increase in the number of identity thefts across all the states in 2020 compared to 2019; the percentage increase ranged from 45% to 1,801.1%. This coincided with the pandemic, which started in December 2019. The top 5 states that had the highest percent increase in 2020 are Kansas, Rhode Island, Maine, Washington, and Illinois. Moreover, in the year 2020, there was a dramatic increase across all the states in the number of identity theft reports related to government documents or benefits fraud, ranging from 207.7% to 33,236% increase compared to the year 2019. This was due to the sudden increase in available funds to help Americans during the pandemic, including unemployment benefits, stimulus checks, small business loans, etc., along with the expedited process to distribute the funds, which created ideal conditions for cybercriminals, especially identity thieves.